Derecho a una suspensión temporal al pago de las pensiones alimenticias mientras el alimentante y alimentado conviven bajo un mismo techo. - Salazar Mena, Erika Kamila (2023)
Food is a necessity for all those who are fed, since it lies in the considerable increase in single mothers who judicially demand the payment of this item to cover the needs of minors. Currently in society there are many mothers who, despite living with the father of minors under the same roof, have an economic alternative to demand this alimony for their children, as this is allowed by the special regulation such as the Childhood and Adolescence Code, therefore it is important to protect the interest of the family, essentially when the father is the one who is traditionally in charge of supporting the family, and living under the same roof it would be unfair for him to have to generate a payment to the mother of his child as he is already supporting nding said home. This research analyzes article 7 of chapter I of title V of the Organic Code of Childhood and Adolescence, in order to determine how the obligee's rights are established in the face of the good coexistence that must exist and the harmonious development of the growth stages of minors. Through the field methodology, it has been possible to carry out this research whose impact on today's society is of considerable importance because women have sought to make a business of their children versus the satisfaction and need for their rights in society because it would be misconceived that alimony would be misused, since the mere fact of living under the same roof forces the obligors to contribute to the maintenance of their family. Keywords: Feeding, fed, good living, maintenance, physical, psychological and emotional integrity.